ANALISIS KARAKTERISITIK KOMPOSIT SERBUK KAYU, SERABUT KELAPA DAN CANGKANG KERANG PADA REM TROMOL SEPEDA MOTOR LISTRIK - Muhamad Abi Yoga (LPPM, Universitas Negeri Jakarta, 2022)
The background of this study was taken to utilize the residual waste produced by wood powder, coconut fiber and green shells. The purpose of this study is to find the best composite variation on electric motorbike brake pads made from wood powder, coconut fiber and green shells powder on bending test, the mass reduction test and braking time. The Experimentation Method used in this reserach was carried out by varying the compositon of the 3 brake pads test specimens namely SK20SKL20CK0R60, SK20SKL20CK10R50 and SK20SKL20CK20R40 then performed bending test, the mass reduction and braking time. Based on the bending test results obtained, the SK20SKL20CK0R60 test specimen has the strongest rate amounted to 186,33 N. then for the mass reduction and braking time value in this study, the test was carried out by taking the test from 3 test laps (track) and carried out 9 times the test (braking) on each lap. Based on the mass reduction test and braking time, the SK20SKL20CK0R60 specimen has the closest indication to standard brake lining value of 0.0066 grams.